2017
DOI: 10.4168/aair.2017.9.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles, a Key Mediator to Link Environmental Microbiota to Airway Immunity

Abstract: Asthma is considered the hallmark of chronic airway inflammation, in which several inflammatory cells of the innate and adaptive immune system act together. The disease is thought to be caused by a combination of genetic and environmental factors; however, precise mechanisms for airway inflammation remain unclear. The human microbiota provides an increasingly favored explanation for inflammatory diseases; an altered microbiota composition has been shown to regulate immune responses. However, given the complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 71 publications
1
16
1
Order By: Relevance
“…The microbiomes detected in the lungs or in urine are representative examples. 9 10 11 12 34 Interestingly, there were notable differences in bacterial composition between urine in this study and skin in the previous study. 35 Staphylococcus was found most commonly in the skin washing fluid of AD patients in our previous study.…”
Section: Discussioncontrasting
confidence: 54%
“…The microbiomes detected in the lungs or in urine are representative examples. 9 10 11 12 34 Interestingly, there were notable differences in bacterial composition between urine in this study and skin in the previous study. 35 Staphylococcus was found most commonly in the skin washing fluid of AD patients in our previous study.…”
Section: Discussioncontrasting
confidence: 54%
“…A study has reported that intraperitoneally injected bacterial EVs spread throughout the mouse body, accumulating in the liver, lung, spleen, and kidney within 3 h of administration 22 . Several studies have also reported that bacteria-derived EVs can be detected in human blood serum, urine, or stool, and have claimed that bacteriaderived EVs are related to the immune response or development of disease [23][24][25][26][27] . For example, studies have shown that EVs derived from Staphylococcus aureus contribute to atopic dermatitis-like skin inflammation 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…These EVs alter the phagocytes' efferocytotic activity [41], which has been linked to the worsening of pathological conditions such as atherosclerosis and chronic obstructive pulmonary disease [51,52]. In addition, through biological pathway analysis, PM exposure seems to modify EV-encapsulated miRNA involved in the maintenance of health [12,42,53].…”
Section: Discussionmentioning
confidence: 99%